2017
DOI: 10.1093/pch/pxx077
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems over a year in sexually abused preschoolers

Abstract: Sexually abused preschoolers are at risk of presenting with sleep problems. These results are worrisome given the negative impacts of sleep problems on child development. Research and clinical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Así se han observado diferencias significativas en la frecuencia de problemas de sueño entre 224 preescolares víctimas de abuso sexual y 83 no víctimas, como son no querer dormir solo, dificultades para conciliar el sueño, pesadillas y terrores nocturnos, sueño interrumpido o dormir menos que otros niños y niñas. Estos problemas no parecen desaparecer con el paso del tiempo y se mantienen un año después de la revelación del abuso según el estudio (Langevin et al, 2017). A su vez, estos problemas de sueño se han asociado con síntomas disociativos en una muestra de 179 niños y niñas víctimas de abuso sexual de entre 3 y 6 años, debiéndose tratar también por su influencia en otras consecuencias de la victimización (Hébert et al, 2017).…”
Section: Indicadores Y Consecuencias De La Victimización Sexual En La...unclassified
“…Así se han observado diferencias significativas en la frecuencia de problemas de sueño entre 224 preescolares víctimas de abuso sexual y 83 no víctimas, como son no querer dormir solo, dificultades para conciliar el sueño, pesadillas y terrores nocturnos, sueño interrumpido o dormir menos que otros niños y niñas. Estos problemas no parecen desaparecer con el paso del tiempo y se mantienen un año después de la revelación del abuso según el estudio (Langevin et al, 2017). A su vez, estos problemas de sueño se han asociado con síntomas disociativos en una muestra de 179 niños y niñas víctimas de abuso sexual de entre 3 y 6 años, debiéndose tratar también por su influencia en otras consecuencias de la victimización (Hébert et al, 2017).…”
Section: Indicadores Y Consecuencias De La Victimización Sexual En La...unclassified
“…Referente a la etapa del desarrollo, se ha observado que cuanto más temprana sea la experiencia de abuso, más probable es que la víctima acabe desarrollando síntomas disociativos (Vonderlin et al, 2018). Específicamente en edad preescolar, los estudios internacionales han descrito que niños/as podrían manifestar principalmente problemas somáticos, retrasos en el desarrollo, problemas internalizantes, síntomas de estrés postraumático y conducta sexualizada (Cantón-Cortés y Cortés, 2015; Echeburúa & De Corral, 2006;Langevin et al, 2017). En etapa escolar se podrían manifestar problemas somáticos y conductas sexuales inapropiadas.…”
Section: Introductionunclassified
“…Symptoms of night terror make up 1.8% versus 0.5%; those of nightmares, 4.4% versus 1.7%; those of early awakening, 3.7% versus 1.9%; and those of daytime sleepiness, 9.9% versus 6.9%. Moreover, SDs are highly prevalent among sexually abused individuals, particularly females in adulthood, and are manifested in an increase of awakenings, nighttime movement, sleep paralysis, nightmares, and insufficient sleep (11,12). A d d i t i o n a l l y, w h e n d e a l i n g w i t h sociodemographic information about the association between child sexual abuse and SDs in preschoolers, there have been negative associations between SDs, maternal age and their education level (12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SDs are highly prevalent among sexually abused individuals, particularly females in adulthood, and are manifested in an increase of awakenings, nighttime movement, sleep paralysis, nightmares, and insufficient sleep (11,12). A d d i t i o n a l l y, w h e n d e a l i n g w i t h sociodemographic information about the association between child sexual abuse and SDs in preschoolers, there have been negative associations between SDs, maternal age and their education level (12). Furthermore, according to the study carried out by Baiden et al, about 11% of men and 17% of women who experienced childhood adversity have shown changes in their daily sleep patterns.…”
Section: Introductionmentioning
confidence: 99%